Physical Simulation of a Nonconsumable Lance for Secondary Refining Operations - Arcos-Gutiérrez, Hugo; Aparicio-Fernández, Rosaura; Barrera-Cardiel, Gerardo; Carreón-Garcidueñas, Héctor Guillermo; Garduño Olvera, Isaías E. (Metallurgical and materials transactions. B, Process metallurgy and materials processing science, 2021)
In this research, the proposal to use a nonconsumable lance or heat pipe to decrease the mixing times in a secondary refining ladle is evaluated. The main idea is to minimize the stirring times to get the complete mixing of liquid steel, mainly due to the fact that a consumable lance once its melted changes the operation conditions. Use of a nonconsumable lance is well known because of its excellent self-protective characteristics; in general, this kind of nonconsumable lance is used in almost any gas injection operation process. Hence, a set of experiments in a physical model demonstrated the viability and competitiveness of the nonconsumable lance in a secondary refining ladle. The results obtained in the physical modeling revealed that the vibration signals, acquired by the accelerometer, are proportional to the amount of agitation energy induced by the injected gas (kinetic and potential energy). Regarding the increment in the vibrations, the inclination angle of the lance showed that the mixing times have a significant effect on the mixing time of the liquid.